2021
DOI: 10.3390/coatings11040457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature on Microstructure and Resistivity of TiC Thin Films

Abstract: Titanium carbide (TiC) thin films were prepared by non-reactive simultaneous double magnetron sputtering. After deposition, all samples were annealed at different temperatures under high-vacuum conditions. This paper mainly discusses the influence of deposition methods and annealing temperatures on microstructure, surface topography, bonding states and electrical resistivity of TiC films. XRD (X-ray diffraction) results show that TiC thin films can still form crystals without annealing, and the crystallinity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The resistivity is 10.5 and 6.93 Ω m × 10 –8 for Pt and Ni, respectively . Moreover, NN15:350 was annealed at 350 °C in the PECVD reactor during synthesis, resulting in an increase in the crystallite grain size, thereby lowering the resistivity. The low resistivity of NN15:350 allows for faster electron transport through the film leading to a lower R Ω compared to that of Ni and Pt, as reflected in Figure b,c. R Ω remains the same with the reaction kinetics of HER and OER.…”
Section: Resultsmentioning
confidence: 99%
“…The resistivity is 10.5 and 6.93 Ω m × 10 –8 for Pt and Ni, respectively . Moreover, NN15:350 was annealed at 350 °C in the PECVD reactor during synthesis, resulting in an increase in the crystallite grain size, thereby lowering the resistivity. The low resistivity of NN15:350 allows for faster electron transport through the film leading to a lower R Ω compared to that of Ni and Pt, as reflected in Figure b,c. R Ω remains the same with the reaction kinetics of HER and OER.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the only variables impacting the results are the film thickness and the temperature utilized in the heat treatment. Moreover, AFM experiments have confirmed that larger roughness tends to escalate in the as-deposited state as well as with lower annealing temperatures and hinder smooth current flow through the film, resulting in a notable increase in the measured value [45][46][47].…”
Section: Electrical Propertiesmentioning
confidence: 91%
“…This increased Fe content in the coating can compromise the protective properties of the Al 2 O 3 coating, Annealing can help minimize the surface energy of the coating by rearranging atoms or molecules, leading to densification and improved packing. It also facilitates the diffusion of atoms or molecules within the coating, allowing pores or voids to collapse [63][64][65]. The reduction in porosity can be accounted for the improved corrosion resistance exhibited by the annealed coating.…”
Section: Electrochemical Corrosion Behavior Of Coatingsmentioning
confidence: 99%